Pengaruh Kejelasan Sasaran Anggaran dan Penerapan Akuntansi Sektor Publik Terhadap Akuntabilitas Kinerja - Septiriane, Sherillia; Nusdal, Yon (Jurnal Riset Akuntansi, 2012)
The purpose of research by the author, to determine the effect of Budget Goal Clarity and Application Public Sector Performance Accounting the Performance Accountability in Parliament Office in Bandung. The research method used is descriptive analysis and verification methods with quantitative approaches. The population in this study were all employees of Sub Division of Budget and Finance Council Bandung totaling 20 people. The sample selection is done by using saturation sampling method with a sample of 20 people where the total population is equal to the number of samples. The analysis model used is multiple linear regression analysis. The results of hypothesis testing in this study showed that Clarity Budget Target has a significant positive effect on Performance Accountability means the obvious target for the budget, it is increasingly easy to be accounted for. Implementation of International Public Sector Accounting has a significant positive effect on Performance Accountability means the better implementation of public sector accounting, the more accountable.